2023
DOI: 10.1111/jcmm.17789
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression profiles of plasma exosomal microRNAs in dilated cardiomyopathy with chronic heart failure

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…Multiple lines of evidence have also been reported, indicating that such exosome-mediated cellular communication is altered and impaired in pathological conditions, particularly in oncogenesis [4,11]. More recently, impaired exosome signaling has also been reported in distinct cardiovascular pathological contexts, including ischemic [67][68][69], electrical [280][281][282][283][284][285][286] and structural [215,223] cardiopathies. It is important to highlight in this context that increasing evidence is reported about the functional role of exosomes in distinct ischemic diseases, such as MI and coronary artery diseases, as well as in structural heart diseases such as DCM and HCM, as reviewed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiple lines of evidence have also been reported, indicating that such exosome-mediated cellular communication is altered and impaired in pathological conditions, particularly in oncogenesis [4,11]. More recently, impaired exosome signaling has also been reported in distinct cardiovascular pathological contexts, including ischemic [67][68][69], electrical [280][281][282][283][284][285][286] and structural [215,223] cardiopathies. It is important to highlight in this context that increasing evidence is reported about the functional role of exosomes in distinct ischemic diseases, such as MI and coronary artery diseases, as well as in structural heart diseases such as DCM and HCM, as reviewed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In order to find biomarkers for DCM diagnosis, Zhang et al (2023) performed isolation of exosomes in patients with chronic heart failure (CHF) caused by DCM. By next generation sequencing, they identified 92 microRNAs differentially expressed, and gene ontology analysis revealed that these microRNAs are related to oxytocin signalling, Hippo signalling and Ras signalling, pointing them out as candidates for CHF diagnosis [223]. As mentioned in previous paragraphs, diabetes mellitus is related with complications in HF with preserved ejection fraction (HFpEF).…”
Section: Small Extracellular Vesicle Transcriptomic Analyses In Heart...mentioning
confidence: 92%
See 2 more Smart Citations
“…A variety of disease activity indexes are established according to the results of clinical, laboratory, and endoscopic examinations, but they are mainly used in clinical trials [ 29 ]. The construction of biomarkers with fewer genes means lower cost and easier access to clinical applications [ 30 , 31 ]. In the time of advocating individualized treatment, it is imperative to determine non-invasive biomarkers to monitor normal people for accurate diagnosis and prevention of UC, so as to optimize the early diagnosis and drug treatment of UC.…”
Section: Discussionmentioning
confidence: 99%